Peran Komunikasi Efektif Dalam Meningkatkan Kepercayaan Masyarakat Terhadap Polri: Studi Kasus Teori Habernas - M. Taufiq Hidayah Tanjung; Perdana, Cuanda Mitra; Muharri; Ahmad Arifin (STAI Bumi Silampari, 2025)
The aim of this research is to examine the role of effective communication in increasing public trust in the National Police based on Habermas' communication theory. This research uses a descriptive qualitative research method with a library research approach, which analyzes relevant literature, such as books, academic journals and research reports. The main data sources come from various references related to effective communication, Habermas' theory, and its application in the context of the National Police. The research results show that communication based on the principles of Habermas's theory, especially regarding transparency, dialogue and equality, can improve the image of the National Police in the eyes of the public. Programs such as dialogical patrols and conveying information through various media have increased public participation in discussing security issues and Polri policies. These findings indicate that responsive and humanistic two-way communication can strengthen relations between the National Police and the community, as well as build public trust in the police institution.